2020
DOI: 10.3389/fneur.2020.569699
|View full text |Cite
|
Sign up to set email alerts
|

Current Conceptual Understanding of the Epileptogenic Network From Stereoelectroencephalography-Based Connectivity Inferences

Abstract: Localization of the epileptogenic zone (EZ) is crucial in the surgical treatment of focal epilepsy. Recently, EEG studies have revealed that the EZ exhibits abnormal connectivity, which has led investigators to now consider connectivity as a biomarker to localize the EZ. Further, abnormal connectivity of the EZ may provide an explanation for the impact of focal epilepsy on more widespread brain networks involved in typical cognition and development. Stereo-electroencephalography (sEEG) is a well-established me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Our third mechanism hypothesized that if strong cortical abnormalities existed beyond the proposed resection site, a localized resection may not fully suppress seizures postsurgically. Widespread abnormalities have been reported previously using diffusion MRI data in epilepsy, 36,37 with some studies attributing widespread abnormalities to an underlying epileptogenic network facilitating the spread of seizures to distant regions 7,38 . Our marker of surgical failure may reflect this epileptogenic network.…”
Section: Discussionsupporting
confidence: 53%
“…Our third mechanism hypothesized that if strong cortical abnormalities existed beyond the proposed resection site, a localized resection may not fully suppress seizures postsurgically. Widespread abnormalities have been reported previously using diffusion MRI data in epilepsy, 36,37 with some studies attributing widespread abnormalities to an underlying epileptogenic network facilitating the spread of seizures to distant regions 7,38 . Our marker of surgical failure may reflect this epileptogenic network.…”
Section: Discussionsupporting
confidence: 53%
“…The source-sink hypothesis is supported by clinical evidence based on the levels of glutamate and glutamate receptors in the brain [55][56][57][58] and iEEG studies that have demonstrated strong inward (inhibitory) connectivity to the EZ regions during rest. 59,60,63,64 We evaluated the predictive value of the SSI by a) rating the correspondence between the hypothesized CA-EZ and regions with high SSIs and b) building a random forest to model the probability of a successful surgery as a function of the source-sink metrics, and compared the performance to that of HFOs, a commonly used interictal iEEG feature. The analysis was performed on data from 65 patients treated across 6 clinical centers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a high inward directed influence to the EZ at rest. 55,[67][68][69] In a recent study Narasimhan et al 67 stated that high inward connectivity may reflect inhibitory input from other regions to prevent the onset and spread of seizure activity, but the direction of these signals may flip when seizure activity begins. This is supported by iEEG studies in neocortical epilepsy demonstrating functional isolation of epileptogenic areas at rest 70,71 and that increased synchronization in seizure-onset regions may be suggestive of an inhibitory surround.…”
Section: Biological Evidence Supporting the Source-sink Hypothesismentioning
confidence: 99%
“…We used a game rule 11 (maximin) to calculate gains across scenarios (random epochs) that represent possible game states, assuming that EN nodes would score better than NN nodes. We expected that far from seizures, EN nodes, which lack part of the regulatory feedback from NN 12 , would be more active but unable to turn the game balance (Figure 1), due to their limited number -the EN is smaller and surrounded by NN. During seizure time, conversely, both EN and NN should display significant connectivity change, the NN counteracting or falling under the influence of the EN (seizure propagation).…”
Section: Parameters So% (Work) Allmentioning
confidence: 99%